Kidney transplantation during coronavirus 2019 pandemic at a large hospital in Miami. Issue 6 (2nd August 2020) - Chandorkar, Aditya; Coro, Ana; Natori, Yoichiro; Anjan, Shweta; Abbo, Lilian M.; Guerra, Giselle; Mattiazzi, Adela D.; Mendez‐Castaner, Lumen A.; Morris, Michele I.; Camargo, Jose F.; Vianna, Rodrigo; Simkins, Jacques
Abstract: Background: Coronavirus 2019 (COVID‐19) pandemic has resulted in more than 350 000 deaths worldwide. The number of kidney transplants has declined during the pandemic. We describe our deceased donor kidney transplantation (DDKT) experience during the pandemic. Methods: A retrospective study was conducted to evaluate the safety of DDKT during the COVID‐19 pandemic. Multiple preventive measures were implemented. Adult patients that underwent DDKT from 3/1/20 to 4/30/20 were included. COVID‐19 clinical manifestations from donors and recipients, and post‐transplant outcomes (COVID‐19 infections, readmissions, allograft rejection, and mortality) were obtained. The kidney transplant (KT) recipients were followed until 5/31/20. Results: Seventy‐six patients received kidneys from 57 donors. Fever, dyspnea, and cough were reported in 1, 2, and 1 donor, respectively. Thirty‐eight (66.6%) donors were tested for Severe Acute Respiratory Syndrome Coronavirus 2 (SARS‐CoV2) prior to donation (mainly by nasopharyngeal or bronchoalveolar lavage polymerase chain reaction [PCR]) and 36 (47.3%) KT recipients were tested at the time of DDKT by nasopharyngeal PCR; all of these were negative. Our recipients were followed for a median of 63 (range: 33‐91) days. A total of 42 (55.3%) recipients were tested post‐transplant for SARS‐CoV2 by nasopharyngeal PCR including 12 patients that became symptomatic; all tests were negative except for one that was inconclusive, but it was repeated and came back negative. Forty (52.6%) KT recipients were readmitted, and 7 (9.2%) had biopsy‐proven rejection during the follow‐up. None of the KT recipients transplanted during this period died. Conclusions: Our cohort demonstrated that DDKT can be safely performed during the COVID‐19 pandemic when preventive measures are implemented.